Attractiveness and retention factors for employed physiotherapists in France: A multicentre survey. - Aurélien Auger; Arnaud Delafontaine; Jeanne Lecordier; Thomas Rulleau; François-Régis Sarhan (PLoS ONE, 2025)
Objectives The aim of this study was to investigate the factors influencing the attractiveness of employed physiotherapy, considering the shortage of physiotherapists in the salaried sector, previously unsuccessful measures. Methods A survey was conducted using an online self-administered questionnaire. The primary outcome measure involved assessing respondents' agreement with each statement in key domains. Regarding the secondary outcome measures, the relationships between respondents' age and their responses, as well as the relationship between their profession and their responses, were examined. Results The study included 448 participants in France, encompassing both primary and secondary care settings. The sample consisted of practicing physiotherapists (83.1%) and healthcare managers (16.9%). Respondents expressed significant concerns regarding the attractiveness of employed physiotherapy. For the primary outcome, the study identified potential solutions, including improving financial recognition, promoting continuous professional development, and enhancing inclusion in healthcare projects. For the secondary outcomes, statistically significant relationships were found between respondents' age and their answers for variables 16 (additional qualifications; p = 0.048), 24 (work-life balance; p = 0.010), and 25 (professional quality of life; p = 0.0005). Conclusion The findings underscore the need to enhance financial recognition, support continuous professional development, and increase inclusion in healthcare projects to effectively improve the attractiveness of employed physiotherapy. These results have significant implications for policymakers and healthcare institutions grappling with recruitment challenges. Further research and collaborative efforts are crucial to implementing the recommended measures and assessing their impact on the employed physiotherapy profession.